The Life We Live and the Life We Experience: Introducing the Epistemological Difference between"Lifeworld" (Lebenswelt) and"Life Conditions" (Lebenslage) - Björn Kraus (Social Work and Society)
The lifeworld term and the programmatic demand for lifeworld-orientation are well established within the entire field of modern day social work. The subject of this article is the introduction of a lifeworld-concept, that is based on an epistemological distinction between"lifeworld" (Lebenswelt) and"life conditions" (Lebenslage). In this context, the term"lifeworld" and its usage will be critically reconsidered and then contrasted to the term"life conditions". By taking a closer look at the differentiation between the life we live (i.e. the live as it happens), the life we experience and the life which we communicate to others, it becomes possible to demonstrate the specific borders and requirements of perception and communication, which have to be handled responsibly in research, teaching and practical work in order to meet professional, legal and normative standards.